What if Trading Location Is Different from Business Location? Evidence from the Jardine Group - Chan, Kalok; Hameed, Allaudeen; Lau, Sie Ting (Journal of Finance, 2003)
Abstract We examine the price behavior and market activity of the Jardine Group companies after they were delisted from Hong Kong in 1994. Although the trading activity of the Jardine Group moved to Singapore, the core businesses remained in Hong Kong and Mainland China. Evidence indicates the Jardine stocks are correlated less (more) with the Hong Kong (Singapore) market after the delisting. This result cannot be explained by various hypotheses, such as relocation of core business, time‐varying betas, migration of trading activity, and currency and tax distortions. We conclude that price fluctuations are affected by country‐specific investor sentiment.